Justifying human rights: does consensus matter? - Kim, Eun-Jung Katherine (Human rights review, 2012)
This paper is a critical examination of a widely accepted method of human rights justification. The method defends the universality of human rights by appeal to diverse worldviews that converge on human rights norms. By showing that the norms can be justified from the perspective of diverse worldviews, human rights theorists suggest that there is reason to believe that human rights are universal norms that should govern the institutions of all societies. This paper argues that the evidence of plural foundations of human rights fails to increase our confidence in the universality of human rights. The paper defends the following claims: (1) the convergence on human rights is better explained as an accidental outcome than as an indicator of the universality of human rights, (2) the plurality of human rights justification is superfluous to the explanation of why human rights apply to all societies, (3) the aggregation of justifications decreases rather than increases the reliability of the universality belief, and (4) the reasonable disagreement among conflicting justifications generates an epistemic dilemma.